The Hindu marriage system in Bangladesh: addressing discrimination - Zahur, Mahua (© 2014 Commonwealth Secretariat, 2016)
This article was published in the Commonwealth Law Bulletin [© 2014 Commonwealth Secretariat.] and the definite version is available at: http://dx.doi.org/10.1080/03050718.2014.971837 The Journal's website is at: http://www.tandfonline.com/doi/abs/10.1080/03050718.2014.971837